ANALISIS STRATEGI PEMASARAN UNTUK MENINGKATKAN PEJUALAN JANGKRIK PADA PERUSAHAAN MAJA FARM DI PESAWARAN (Universitas Mitra Indonesia, 2021)
ABSTRACT The Maja Farm company in Pesawaran is engaged in, is an individual company engaged in animal husbandry, namely cricket farming. This company is located in Taman Sari Village, Gedung Tataan District, Pesawaran Regency. The Maja Farm company is currently experiencing problems with a decline in sales value from 2018 of 64.9% and in 2019 the percentage decreased to 30.4%. This research was conducted to analyze suitable marketing strategies to increase sales value at Maja Farm Company in Pesawaran. The analytical tool used in this research is SWOT analysis. From the results of IFAS calculations, the total value is 2.80 and EFAS with a total value of 2.55, from these results in the position where the company is in cell 5, namely the integration strategy through horizontal integration or disruption. From the result of the SWOT matrix combination, the most dominant strategy is SO, with a total of 3.55 and a strategy of ST 2.80. Keywords: Marketing Strategy, Sales, SWOT analysis